Prevalence of Onchocerciasis Syndrome in Ise-Orun Local Government Area of Ekiti State, Nigeria (Biological Sciences - PJSIR, 2005)
Twenty seven towns and villages in the Ise-Orun local government area of Ekiti State, Nigeria are in the grip of onchocerciasis. Out of the 2045 subjects examined, 1131 (55.3% at 95% confidence interval- CI, 0.53-0.57) were found to be infected by the disease. The prevalence of onchocerciasis varied from one town or village to the other in the area of study. The peak prevalence (80.5% at 95% CI, 0.73-0.89) was recorded in the village Temidire. The people aged 50-59 years accounted for peak prevalence (72.0% at 95% CI, 0.63-0.81). Out of the total 2045 subjects examined, 51.0, 26.8,19.2 and 3.0% were, respectively, found to be suffering from craw-craw, leopard skin, nodules, and partial blindness.